Pengaruh penambahan filler kapur dan kaolin terhadap kekerasan dan pukul takik kompon PVC - Karani, Sofyan; Yuniari, Arum (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1990)
The objective of this study is to detect whether there is any influence on the physical quality of the PVC compound (hardness and impact resistant). Which CaCO3, kaolin and mixture of CaCO3 and kaolin as filler is added into the batch. The more the filler added into the batch, the higher the hardness will be. The highest figure of the test result can be presented as follow : with the addition of 135 phr CaCO3 as filler the hardness is 71,2 shore D, addition 135 phr CaCO3 as filler the hardness is 74,0 shore D, while with the addition of 55 phr CaCO3 and 80 phr kaolin, the hardness is 77,0 shore D.The more the CaCO3 filler added into the bath, the higher the impact resistance will be, whereas the more the kaolin as filler added the lower the impact resistance will be. By the addition 135 phr of CaCO3, the highest figure of the impact resistance is 4,34 kg cm/cm and by the addition of kaolin the highest figure is 1,99 kg cm/cm with 75 phr kaolin.While by the addition of the mixture of 40 phr CaCO3 and 50 phr kaolin as filler, the highest figure is achieved at 2,98a kg cm/cm, and after that it will be decreasede.Â INTISARIÂ Penelitian ini bertujuan untuk mengetahui pengaruh penambahan filler kapur, kaolin dan filler campuran akpur dengan kaolin kekerasan dan ketahanan pukul takik kompon PVC.Kekerasan makin tinggi dengan bertambahnya pemakaian filler, kekerasan tertinggi untuk filler kapur adalah 71,2 Shore D pada penambahan 135 phr dan untuk filler kaolin adalah 74,0 Shore D pada penambahan 135 phr, sedangkan untuk filler campuran kekerasan tertinggi adalah 77,0 Shore D pada penambahan kapur 55 phr dengan kaolin 80 phr.Ketahanan pukul takik untuk filler kapur makin tinggi dengan bertambahnya pemakaian filler, dan untuk filler kaolin pemakaian makin bertamb ah ketahanan pukul takik makin rendah. Ketahanan pukul takik tertinggi untuk filler kapur adalah 4,34 kg cm/cm pada penambahan 135 phr dan untuk filler kaolin ketahanan pukul takik tertinggi adalah 1,99 Â kga cm/cm pada penambahan 75 phr. Sedangkan untuk pemakaian filler campuran kapur dan kaolin ketahanan pukul takik naik sampai pemakaian kapur 40 phr dan kaolin 50 phr, yaitu 2,98 kg cm/cm, kemudian akan menurun